A comparative analysis of factors determining the value of the Indonesian Sharia Stock Index (ISSI) before and after the Covid-19 - Franadita, Dwi; Daulay, Aqwa Naser; Dharma, Budi (Universitas Islam Indonesia, 2024)
IntroductionThe Covid-19 pandemic had profound impacts on global financial markets, prompting extensive research to understand how various economic sectors, including sharia-compliant stocks, responded to the crisis. ObjectivesThis study aims to compare the determinant factors affecting the ISS (Indonesian Sharia Stock Index) during the periods before and after Covid-19 in Indonesia.MethodA descriptive and verificative quantitative research method was employed, validating collected data and examining the relationships between variables using statistical procedures to test research hypotheses. The data sources utilized were secondary data published by the Indonesia Stock Exchange (IDX). Data analysis techniques included Normality Tests and Paired Sample T-tests. Data processing was assisted by SPSS for Windows Version 22.00. The sample comprised data from the Indonesian Sharia Stock Index before and after Covid-19, covering the period from 2018 to 2022.ResultsThe study's findings indicate an increase in the Indonesian Sharia Stock Index post-Covid-19, with a significant difference observed before and after Covid-19.ImplicationsThe significant increase in the Indonesian Sharia Stock Index post-Covid-19 implies that sharia-compliant investments demonstrated resilience and potential for recovery in the face of economic disruptions, highlighting their viability as a robust investment option during and after financial crises.Originality/NoveltyThis study provides a novel comparative analysis of the factors influencing the Indonesian Sharia Stock Index before and after Covid-19, offering new insights into the pandemic's differential impact on sharia-compliant financial instruments.